Devaluation, Relative Prices, and International Trade : Evidence From Developing Countries - Reinhart, Carmen (IMF Working Papers; Working Paper ;, 1994)
Devaluation is an integral part of adjustment in many developing countries, particularly relied upon by countries facing large external imbalances. A devaluation can only reduce trade imbalances if it translates to a real devaluation and if trade flows respond to relative prices in a significant and predictable manner. However, a recent strand in the empirical trade literature has questioned the existence of a stable relationship between trade flows and its traditional determinants. This paper re-examines the relationship between relative prices and imports and exports in a sample of 12 developing countries.